PENGEMBANGAN POTENSI EKOWISATA DI DESA TALAGA PACA KABUPATEN HALMAHERA UTARA - Pasto Pasto; Ferdinand Kerebungu; Hamdi Gugule (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
This research problem is the development of potential talaga paca tourist attractions and the setup of infrastructure infrastructure and tourism facilities in the village of talaga paca northern halmahera district. The study aims to describe the inhibitory and contributing factors in the development of the objectives for tourism in the village of talaga paca (a) the potential for tourism (b) the potential tourist infrastructure (c) the benefits and fungus tourism for community life, and the study USES a qualitative method. The results of this study show that. (a) the lack of awareness of tourism's potonsi on terms of infrastructure that still lack. (b) governments should always come down to socializing with tourism (c) in order to better understand the benefits and functions of tourism to their host lives (d), and communities should have access Competitiveness with the development of the current globalization.